2021
DOI: 10.1212/wnl.0000000000012775
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Symptom Onset in Sporadic Alzheimer Disease With Amyloid PET

Abstract: Objective:To predict when cognitively normal individuals with brain amyloidosis will develop symptoms of Alzheimer disease (AD).Methods:Brain amyloid burden was measured by amyloid PET with Pittsburgh compound B. The mean cortical standardized uptake value ratio (SUVR) was transformed into a timescale using longitudinal data.Results:Amyloid accumulation was evaluated in 236 individuals who underwent more than one amyloid PET scan. The average age was 66.5 ± 9.2 years and twelve individuals (5%) had cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 50 publications
6
65
0
Order By: Relevance
“…For this reason and because direct comparisons of factors that affect PET detection limits and variability were not available across cohorts, we used previously validated methods and A+ thresholds from each cohort that minimize PET binding estimate variance and used a study design focused on replicating findings across cohorts and methods rather than attempting pooled analyses across cohorts. As in our previous work 13 and a recently published similar work 14 estimating individualized EAOA in people who are A+ enables estimation of A+ disease duration from a single amyloid PET scan. This ability to define disease time from amyloid PET provides new insights into how known and unknown factors affect dementia risk and timing in Alzheimer's disease, which has clinical trial implications.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For this reason and because direct comparisons of factors that affect PET detection limits and variability were not available across cohorts, we used previously validated methods and A+ thresholds from each cohort that minimize PET binding estimate variance and used a study design focused on replicating findings across cohorts and methods rather than attempting pooled analyses across cohorts. As in our previous work 13 and a recently published similar work 14 estimating individualized EAOA in people who are A+ enables estimation of A+ disease duration from a single amyloid PET scan. This ability to define disease time from amyloid PET provides new insights into how known and unknown factors affect dementia risk and timing in Alzheimer's disease, which has clinical trial implications.…”
Section: Discussionmentioning
confidence: 68%
“…Similar findings regarding age, but not APOE or sex were recently reported using a similar approach. 14 EAOA shortening the preclinical timeframe may be explained by age-associated increases in comorbidity with other age-related diseases such as vascular disease and other neurodegenerative proteinopathies that co-occur in Alzheimer's disease. 52 APOE-e4 carriage shortening the preclinical timeframe could represent a pleiotropic susceptibility effect of APOE on brain health since APOE is also implicated in cerebrovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models will be helpful to elucidate the cellular and sub-cellular locations of changes in glycolysis in the context of AD pathology. The concept that youthful patterns of brain AG might reflect greater metabolic resilience to amyloid pathology might also help to explain why, at equivalent burdens of brain amyloid pathology, both chronological and brain age have been associated with an increased risk of cognitive impairment [39][40][41] . On the other hand, in young adults prior results have shown that brain amyloid preferentially deposits at sites of higher AG 22,23 ; thus, the relationship between amyloid deposition and AG could well be bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“… 4 and Lim and Mormino; 39 see also Schindler et al. 40 ), or no difference in amyloid accumulation by APOE ε4 genotype. 4 , 41 , 42 Our findings suggest that observed differences in Aβ 42 /Aβ 40 trajectories between APOE ε4 carriers and non‐carriers reflect higher rates and earlier ages of amyloid positivity among APOE ε4 carriers (resulting in a more advanced preclinical disease stage).…”
Section: Discussionmentioning
confidence: 91%